2000
DOI: 10.1055/s-2008-1072394
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoid Tumors of the Appendix in Children - Epidemiology, Clinical Aspects and Procedure

Abstract: The youngest patient with a metastasizing carcinoid tumor of the appendix reported in the literature was 19 years old. Nevertheless, all younger patients should undergo regular follow-ups; this is done in our department by serum serotonin and chromogranin A determination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 6 publications
1
38
0
Order By: Relevance
“…The rate of aNENs presence in patients undergoing appendicectomy is reported to be 0.3-0.9% (Moertel et al 1968, Connor et al 1998, Tchana-Sato et al 2006, Debnath et al 2008, In't Hof et al 2008, Shapiro et al 2010, Yilmaz et al 2013; however, in some series, it has been reported to be as high as 2.3% (Hatzipantelis et al 2010, Ozer et al 2011, Van Gompel et al 2007 or as low as 0.16% (Coskun et al 2006, Doede et al 2000. The prevalence of aNENs among primary malignant lesions of the appendix ranges between 43 and 57% (Schmutzer et al 1975, Connor et al 1998.…”
Section: Epidemiologymentioning
confidence: 94%
“…The rate of aNENs presence in patients undergoing appendicectomy is reported to be 0.3-0.9% (Moertel et al 1968, Connor et al 1998, Tchana-Sato et al 2006, Debnath et al 2008, In't Hof et al 2008, Shapiro et al 2010, Yilmaz et al 2013; however, in some series, it has been reported to be as high as 2.3% (Hatzipantelis et al 2010, Ozer et al 2011, Van Gompel et al 2007 or as low as 0.16% (Coskun et al 2006, Doede et al 2000. The prevalence of aNENs among primary malignant lesions of the appendix ranges between 43 and 57% (Schmutzer et al 1975, Connor et al 1998.…”
Section: Epidemiologymentioning
confidence: 94%
“…Appendiceal carcinoids are rare and are usually incidental findings following an appendicectomy for acute appendicitis. The overall frequency is 0.2% in more than 350,000 appendicectomies, while the frequency in children has been reported to be 0.169% of all appendicectomies …”
Section: Introductionmentioning
confidence: 97%
“…Appendiceal carcinoids were found in 0.2-0.8 % of resected appendices in two pediatric series (Volpe et al 2000 ;Doede et al 2000 ). In most instances, carcinoids are discovered in appendectomies performed clinically for acute appendicitis, and the fi nding of a carcinoid tumor is unexpected.…”
Section: Etiologymentioning
confidence: 99%
“…Most patients did not have any surgery beyond their original appendectomies (Prommegger et al 2002 ;Dall'Igna et al 2005 ;Hatzipantelis et al 2010 ) (Doede et al 2000 ;Andersson and Bergdahl 1977 ;Corpron et al 1995 ;Parkes et al 1993 ;Ryden et al 1975 ). In eight clinical series from disparate institutions in Europe and North America totaling 194 cases of pediatric appendiceal carcinoid tumors, there were no deaths attributed to the disease.…”
Section: Treatmentmentioning
confidence: 99%